Beauty and The Beast [videorecording (Blu-Ray + DVD)] - Trousdale, Gary (Disney DVD., 1991)
Be our guest at the enchanted 25th Anniversary celebration, a groundbreaking star in the legacy of animation and a new addition to The Walt Disney Signature Collection. Cast a spell on your imagination and embark on an epic adventure with Belle, our brave and independent heroine, the Beast, who has the heart and soul of a prince, the music you'll never forget and all the fun characters you love.